Glioblastoma Treatment and Quality of Life in Children: A Review - Ahmed Ali Al Saleem et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Glioblastoma (GBM) is an aggressive and rare brain tumor in children, with significantly different biological and clinical features compared to adult GBM. Despite advances in treatment modalities, the prognosis for pediatric GBM remains poor, and the aggressive nature of therapies often impacts the quality of life (QoL) in affected children. This review discusses current treatment strategies, including surgery, radiotherapy, and chemotherapy, alongside emerging therapies such as immunotherapy and targeted approaches. Additionally, it evaluates the impact of these treatments on the quality of life, focusing on neurocognitive, emotional, and social aspects, and the importance of supportive care. Received Date: November 06, 2024 Accepted Date: November 27, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/255 https://doi.org/10.5281/zenodo.14251321